Friction material and preparation method thereof, brake pad, brake friction pair and vehicle

By using friction materials of modified phenolic resin, metal reinforced fiber and three-dimensional layered graphite carbon powder in the carbon ceramic brake friction pair, the problem of excessive temperature rise of the carbon ceramic friction pair is solved, and high thermal conductivity and stability are achieved The friction coefficient improves the heat resistance and thermal conductivity of the brake pads.

CN119432003APending Publication Date: 2025-02-14HUNAN JINLI HIGH TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411366765.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Due to the low density and small heat capacity per unit volume, the carbon ceramic brake friction pair leads to a higher friction temperature under the same brake energy, affecting the friction coefficient and braking efficiency of the brake pads.

Method used

Using specific proportions of modified phenolic resin, metal reinforcement fiber, friction enhancer, filler and graphite carbon powder with three-dimensional layered structure, friction materials are prepared through hot pressing and resin curing processes to form a high thermal conductivity and stable friction platform. Brake pads.

Benefits of technology

It effectively improves the thermal conductivity and stability of friction coefficient of friction materials, inhibits rapid heating of friction surfaces, prevents thermal decomposition and wear, improves the heat resistance and thermal conductivity of the brake pads, and solves the temperature rise of the traditional carbon ceramic friction pair. Fast causes degradation in braking performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a friction material and a preparation method thereof, a brake pad, a brake friction pair and a vehicle. The friction material is prepared from the following components in parts by mass: 15 to 25 parts of phenolic resin, 10 to 20 parts of metal reinforced fiber, 10 to 25 parts of friction increasing agent, 10 to 40 parts of filler and 20 to 30 parts of graphite carbon powder, the length-diameter ratio of the metal reinforced fibers is 150-200, the length of the metal reinforced fibers is 5-9 mm, the graphite carbon powder is of a three-dimensional layered structure, and the heat conductivity coefficient of the graphite carbon powder is 400-600 W / m.degree. The metal reinforced fibers with a specific length-diameter ratio and a specific length are matched with the modified phenolic resin, so that the heat-conducting property of the friction material can be effectively improved, a stable friction platform can be formed, and the stability of a friction coefficient is effectively improved; and the graphite carbon powder with a specific heat conductivity coefficient is matched, and the graphite carbon powder has a three-dimensional graphite layered structure, so that rapid temperature rise of the friction surface is effectively inhibited, and rapid thermal decomposition wear of the friction surface is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials, and in particular to a friction material and a preparation method thereof, a brake pad, a brake friction pair and a vehicle. Background Art

[0002] The carbon-ceramic brake friction pair is mainly composed of a carbon-ceramic brake disc and a matching brake pad. The carbon-ceramic brake disc has the advantages of low density, light weight, high temperature resistance, wear resistance, and no corrosion. Compared with the traditional cast iron brake disc, it is known as the first-generation brake disc for new energy vehicles. However, due to its low density, carbon-ceramic materials have a problem of low heat capacity per unit volume. Under the same braking energy, the friction temperature rise between the brake disc and the brake pad friction surface in the carbon-ceramic friction pair is higher than that of the cast iron brake friction pair. The high temperature rise will cause the friction surface layer of the brake pad containing organic materials to decompose due to heat, and the friction coefficient will decrease, thus affecting the braking performance.

[0003] Therefore, it is necessary to improve the traditional technology. Summary of the invention

[0004] Based on this, the present application provides a friction material with strong thermal conductivity and good friction coefficient stability, a preparation method thereof, a brake pad, a brake friction pair and a vehicle.

[0005] The technical solution of this application to solve the above technical problems is as follows.

[0006] In a first aspect, the present application provides a friction material, which comprises the following components by mass:

[0007] 15-25 parts of phenolic resin, 10-20 parts of metal reinforcing fiber, 10-25 parts of friction enhancer, 10-40 parts of filler and 20-30 parts of graphite carbon powder; the aspect ratio of the metal reinforcing fiber is 150-200, the length is 5 mm-9 mm, the graphite carbon powder has a three-dimensional layered structure, and the thermal conductivity of the graphite carbon powder is 400-600 W / m·degree.

[0008] In some embodiments, the friction material includes the following components by weight:

[0009] 18-22 parts of phenolic resin, 12-18 parts of metal reinforcing fiber, 11-24 parts of friction enhancer, 20-30 parts of filler and 24-30 parts of graphite carbon powder.

[0010] In some of the embodiments, in the friction material, the mass ratio of the metal reinforcing fiber to the modified phenolic resin is 0.5-1.25:1.

[0011] In some of the embodiments, in the friction material, the metal reinforcing fiber includes at least one of steel fiber, copper fiber, aluminum fiber and zinc fiber.

[0012] In some embodiments, in the friction material, the particle size of the graphite carbon powder is 5 μm to 10 μm; and / or

[0013] The graphitization degree of the graphite carbon powder is 90% to 96%.

[0014] In some embodiments, in the friction material, the phenolic resin includes a modified phenolic resin, and the modified phenolic resin includes at least one of a molybdenum-modified phenolic resin, a boron-modified phenolic resin, an aniline-modified phenolic resin and a melamine-modified phenolic resin; and / or

[0015] The particle size of the phenolic resin is 50 μm to 80 μm.

[0016] In some embodiments, in the friction material, the friction enhancer includes at least one of magnesium oxide, zirconium oxide, red iron, black iron, zirconium silicate, brown corundum, aluminum oxide and silicon carbide; and / or

[0017] The filler includes at least one of talc powder, precipitated barium sulfate, barite powder, calcium carbonate, calcium hydroxide, mica powder, vermiculite powder, kaolin, diatomaceous earth, antimony sulfide and tin sulfide.

[0018] A second aspect of the present application provides a method for preparing a friction material, comprising the following steps:

[0019] Providing raw materials according to the components of the friction material mentioned above;

[0020] The various raw materials are mixed to obtain a friction material.

[0021] A third aspect of the present application provides a brake pad comprising the above-mentioned friction material.

[0022] A fourth aspect of the present application provides a brake friction pair, including the above-mentioned brake pad.

[0023] A fifth aspect of the present application provides a vehicle comprising at least one of the above-mentioned brake pads and the above-mentioned brake friction pairs.

[0024] Compared with the prior art, the friction material of the present application has the following beneficial effects:

[0025] The friction material of the present application comprises a specific proportion of modified phenolic resin, metal reinforcing fiber, friction enhancer, filler and graphite powder. The modified phenolic resin is combined with metal reinforcing fiber of specific aspect ratio and specific length, which can effectively improve the thermal conductivity of the friction material and form a stable friction platform, thereby effectively improving the stability of the friction coefficient. The graphite powder with a specific thermal conductivity and a three-dimensional graphite layered structure can form a three-dimensional network channel for transmitting friction heat from the friction surface to the inside of the material, thereby effectively inhibiting the rapid heating of the friction surface and preventing the friction surface from rapid thermal decomposition and wear. At the same time, the three-dimensional layered structure can effectively enhance the lubrication ability of the friction material and prevent the friction surface from abnormal mechanical peeling and wear.

[0026] The specific components of the above-mentioned friction material are matched with each other in specific proportions, so that the brake pad prepared by the friction material has high shear strength, good heat resistance, strong thermal conductivity, good friction coefficient stability, and less wear, which effectively solves the problem of the reduction of braking performance of the brake pad due to the rapid temperature rise of the traditional carbon-ceramic friction pair. DETAILED DESCRIPTION

[0027] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0028] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0030] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0031] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0032] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0033] An embodiment of the present application provides a friction material, which comprises the following components by mass:

[0034] 15-25 parts of phenolic resin, 10-20 parts of metal reinforcing fiber, 10-25 parts of friction enhancer, 10-40 parts of filler and 20-30 parts of graphite carbon powder; the aspect ratio of the metal reinforcing fiber is 150-200, the length is 5 mm-9 mm, the graphite carbon powder has a three-dimensional layered structure, and the thermal conductivity of the graphite carbon powder is 400-600 W / m·degree.

[0035] The friction material of the present application comprises a specific proportion of modified phenolic resin, metal reinforcing fiber, friction enhancer, filler and graphite powder. The modified phenolic resin is combined with metal reinforcing fiber of specific aspect ratio and specific length, which can effectively improve the thermal conductivity of the friction material and form a stable friction platform, thereby effectively improving the stability of the friction coefficient. The graphite powder with a specific thermal conductivity and a three-dimensional graphite layered structure can form a three-dimensional network channel for transmitting friction heat from the friction surface to the inside of the material, thereby effectively inhibiting the rapid heating of the friction surface and preventing the friction surface from rapid thermal decomposition and wear. At the same time, the three-dimensional layered structure can effectively enhance the lubrication ability of the friction material and prevent the friction surface from abnormal mechanical peeling and wear.

[0036] The specific components of the above-mentioned friction material are matched with each other in specific proportions, so that the brake pad prepared by the friction material has high shear strength, good heat resistance, strong thermal conductivity, good friction coefficient stability, and less wear, which effectively solves the problem of the reduction of braking performance of the brake pad due to the rapid temperature rise of the traditional carbon-ceramic friction pair.

[0037] It can be understood that in the friction material, by weight, the phenolic resin includes but is not limited to 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts; the metal reinforcing fiber includes but is not limited to 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts; the friction enhancer includes but is not limited to 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts of fillers; 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts of graphite powder; the aspect ratio of metal reinforcing fiber includes but is not limited to 150, 160, 170, 180, 190, 200; the length of metal reinforcing fiber includes but is not limited to 5mm, 6 mm, 7 mm, 8 mm, 9 mm; the thermal conductivity of graphite carbon powder includes but is not limited to 400 W / m·degree, 420 W / m·degree, 450 W / m·degree, 480 W / m·degree, 500 W / m·degree, 520 W / m·degree, 550 W / m·degree, 580 W / m·degree, 600 W / m·degree; in some examples, it can be within the range consisting of any two of these point values ​​as end values, the same below.

[0038] In some of the examples, the friction material includes the following components by weight:

[0039] 18-22 parts of phenolic resin, 12-18 parts of metal reinforcing fiber, 11-24 parts of friction enhancer, 20-30 parts of filler and 24-30 parts of graphite carbon powder.

[0040] In some of the examples, the mass ratio of the metal reinforcing fiber to the modified phenolic resin in the friction material is 0.5~1.25:1.

[0041] It can be understood that in the friction material, the mass ratio of the metal reinforcing fiber to the modified phenolic resin includes but is not limited to 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, and 1.25:1.

[0042] In some of these examples, the mass ratio of the metal reinforcing fiber to the modified phenolic resin in the friction material is 0.7~1:1.

[0043] By controlling the mass ratio of the metal reinforcing fiber to the modified phenolic resin, it is possible to avoid that an excessive amount of the modified phenolic resin attacks the friction material, causing wear of the brake pad and loud noise.

[0044] In some of the examples, in the friction material, the metal reinforcing fiber includes at least one of steel fiber, copper fiber, aluminum fiber, and zinc fiber.

[0045] In some of the examples, in the friction material, the metal reinforcing fiber includes at least one of steel fiber, aluminum fiber, and zinc fiber.

[0046] In some of these examples, the particle size of graphite carbon powder in the friction material is 5μm~10μm.

[0047] It can be understood that in the friction material, the particle size of the graphite carbon powder includes but is not limited to 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0048] In some of these examples, the degree of graphitization of the graphite carbon powder in the friction material is 90% to 96%.

[0049] It can be understood that in the friction material, the graphitization degree of the graphite carbon powder includes but is not limited to 90%, 91%, 92%, 93%, 94%, 95%, and 96%.

[0050] In some of these examples, the friction material includes graphite carbon powder having a highly textured microstructure.

[0051] It is understood that graphite carbon powder includes a by-product of preparing carbon / carbon composite materials by chemical vapor deposition.

[0052] In some of these examples, the preparation of graphite carbon powder in the friction material includes the following steps:

[0053] The carbon source is subjected to chemical vapor deposition and graphitization treatment, and graphitized pyrolytic carbon is deposited on the wall of a deposition crucible barrel; the graphitized pyrolytic carbon is crushed by ball milling to prepare graphite carbon powder.

[0054] It is understood that the carbon source includes but is not limited to at least one of methane, acetylene and propane.

[0055] In some specific examples, the chemical vapor deposition conditions include: the flow rate of the carbon source gas is 1~20m 3 / h, the deposition heating rate is 40~80℃ / h, the deposition temperature is 1000~1200℃, and the deposition pressure is 2.0~10.0kPa.

[0056] In some specific examples, the conditions of the graphitization treatment include: the temperature of the graphitization heat treatment is 2500-3000° C., the insulation time is 100-200 hours, and the protective atmosphere is argon.

[0057] It can be understood that the above-mentioned method for preparing graphite carbon powder can produce the graphite carbon powder in the above-mentioned friction material.

[0058] It can be understood that the graphite powder after ball milling is subjected to electromagnetic impurity removal to remove impurities such as iron and iron oxides in the graphite powder.

[0059] In some of these examples, in the friction material, the phenolic resin includes a modified phenolic resin.

[0060] In some examples, in the friction material, the modified phenolic resin includes at least one of a molybdenum-modified phenolic resin, a boron-modified phenolic resin, an aniline-modified phenolic resin, and a melamine-modified phenolic resin.

[0061] In some of the examples, in the friction material, the modified phenolic resin includes two of a molybdenum-modified phenolic resin, a boron-modified phenolic resin, an aniline-modified phenolic resin, and a melamine-modified phenolic resin.

[0062] In some of the examples, the particle size of the phenolic resin in the friction material is 50 μm to 80 μm.

[0063] It can be understood that in the friction material, the particle size of the phenolic resin includes but is not limited to 50 μm, 60 μm, 70 μm, 80 μm, and 80 μm.

[0064] In some of the examples, in the friction material, the friction enhancer includes at least one of magnesium oxide, zirconium oxide, red iron, black iron, zirconium silicate, brown corundum, aluminum oxide, and silicon carbide.

[0065] In some examples, in the friction material, the filler includes at least one of talc powder, precipitated barium sulfate, barite powder, calcium carbonate, calcium hydroxide, mica powder, vermiculite powder, kaolin, diatomaceous earth, antimony sulfide and tin sulfide.

[0066] An embodiment of the present application provides a method for preparing a friction material, comprising the following steps:

[0067] Providing raw materials according to the components of the friction material mentioned above;

[0068] The various raw materials are mixed to obtain a friction material.

[0069] An embodiment of the present application provides a brake pad including the above-mentioned friction material.

[0070] In some examples, the material of the brake pad may be the above-mentioned friction material, that is, the brake pad is directly prepared using the above-mentioned friction material. In other embodiments, the material of the brake pad may include other materials in addition to the above-mentioned friction material.

[0071] The brake pads prepared with the above friction materials have higher shear strength, better heat resistance, stronger thermal conductivity, better friction coefficient stability, less wear, and effectively solve the problem of reduced braking performance of brake pads caused by excessive temperature rise of traditional carbon-ceramic friction pairs.

[0072] An embodiment of the present application provides a method for preparing a brake pad, comprising the following steps:

[0073] S10: providing raw materials according to the components of the friction material;

[0074] S20: mixing the raw materials to obtain a friction material;

[0075] S30: hot pressing the friction material to prepare a brake pad blank;

[0076] In some of the examples, in step S30, a constant pressure hot press is used for hot pressing.

[0077] In some examples, in step S30, the unit area pressing pressure of the hot pressing molding is 30 Mpa / m 2 ~50Mpa / m 2 .

[0078] Optionally, in step S30, the pressing pressure per unit area of ​​the hot pressing molding is 35 Mpa to 45 Mpa.

[0079] In some of the examples, in step S30, the temperature of the hot pressing molding is 140°C to 160°C.

[0080] Optionally, in step S30, the temperature of hot pressing is 150°C to 155°C.

[0081] In some of the examples, in step S30, the hot pressing molding includes cyclic steps of pressurizing and venting.

[0082] S40: curing the brake pad blank with resin.

[0083] In some of the examples, in step S40, the resin is cured at a temperature of 220° C. to 240° C. for a time of 6 h to 12 h.

[0084] It can be understood that the resin curing temperature includes but is not limited to 220° C., 230° C., and 240° C., and the curing time is 6 h, 8 h, 9 h, 10 h, and 12 h.

[0085] It can be understood that in some examples, after step S40, the method for preparing the brake pad further includes a step of post-processing the cured brake pad, including external dimension processing, wherein the external dimension processing includes rough grinding-grooving-left chamfering-right chamfering-fine grinding. The processed brake pad can also be subjected to infrared ablation, plastic powder electrostatic spraying, riveting of silencers, alarms, springs, inkjet printing, etc.

[0086] An embodiment of the present application provides a carbon-ceramic friction pair, including a carbon-ceramic brake disc and the above-mentioned brake pad.

[0087] The above-mentioned brake pads can effectively solve the problem of the degradation of the braking performance of the brake pads caused by the excessively rapid temperature rise of the traditional carbon-ceramic friction pair.

[0088] An embodiment of the present application provides a vehicle, comprising at least one of the above-mentioned brake pad and the above-mentioned carbon-ceramic friction pair.

[0089] It will be appreciated that means of transportation include but are not limited to cars, sports cars, racing cars, airplanes, high-speed trains, subways, etc.

[0090] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0091] Graphite carbon powder A: A byproduct of chemical vapor deposition of carbon / carbon composite materials. With methane as the carbon source, pyrolytic carbon powder is deposited on the wall of the crucible during chemical vapor deposition. After graphitization treatment at 2800°C for 120 hours and electromagnetic impurity removal, graphite carbon powder A is obtained. The degree of graphitization is 96%, with a complete hexagonal three-dimensional layered structure, a fixed carbon content of 99.99%, a thermal conductivity of 400~600 W / m·degree, and a particle size of 5μm~10μm.

[0092] Example 1

[0093] The raw materials provided are: 20 parts of modified phenolic resin (including 15 parts of molybdenum modified phenolic resin and 5 parts of boron modified phenolic resin), 14 parts of metal reinforcing fiber (including 10 parts of steel fiber, 2 parts of copper fiber and 2 parts of aluminum fiber), 24 parts of friction enhancer (including 5 parts of magnesium oxide, 2 parts of iron oxide, 10 parts of zirconium oxide, 2 parts of zirconium silicate, 2 parts of aluminum oxide and 3 parts of silicon carbide), 22 parts of filler (including 10 parts of precipitated barium sulfate, 2 parts of calcium carbonate, 2 parts of vermiculite and 8 parts of mica powder) and 20 parts of graphite carbon powder A. Among them, the aspect ratio of steel fiber, copper fiber and aluminum fiber in the metal reinforcing fiber is 150 and the length is 5 mm.

[0094] Step 1: Raw material mixing: weighing and mixing the raw materials prepared above in a plowshare mixer to obtain a brake pad mixture;

[0095] Step 2: Hot pressing composite molding: The mixed material obtained in step 1 and the glue-coated steel back are composited on an isotropic hot press to obtain a brake pad blank. Unit area pressure: 45Mpa, pressing temperature: 150℃, exhaust gas program: pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 150 seconds;

[0096] Step 3: Resin curing: The brake pad blank composite-formed in step 2 is fully cured in a program-controlled temperature furnace. The total curing time is 9 hours and the maximum curing temperature is 230 degrees Celsius.

[0097] Step 4: Post-processing: The solidified brake pad blank is processed on a 5-station combination grinder according to the design drawings through rough grinding, grooving, left chamfering, right chamfering and fine grinding. The processed brake pad undergoes infrared ablation, plastic powder electrostatic spraying, and riveting of silencers, alarms, springs, and coding and printing processes to finally obtain the brake pad.

[0098] Example 2

[0099] The raw materials provided are: 21 parts of modified phenolic resin (including 11 parts of boron-modified phenolic resin and 10 parts of aniline-modified phenolic resin), 12 parts of metal reinforcing fiber (including 5 parts of steel fiber, 5 parts of aluminum fiber and 2 parts of zinc fiber), 11 parts of friction enhancer (including 1 part of magnesium oxide, 5 parts of zirconium oxide, 2 parts of aluminum oxide and 3 parts of silicon carbide), 27 parts of filler (including 15 parts of precipitated barium sulfate, 5 parts of calcium carbonate, 2 parts of vermiculite and 5 parts of mica powder) and 30 parts of graphite carbon powder A. Among them, the aspect ratio of steel fiber, zinc fiber and aluminum fiber in the metal reinforcing fiber is 150 and the length is 5 mm.

[0100] Step 1: Raw material mixing: weighing and mixing the raw materials prepared above in a plowshare mixer to obtain a brake pad mixture;

[0101] Step 2: Hot pressing composite molding: The mixed material obtained in step 1 and the glue-coated steel back are composited on an isotropic hot press to obtain a brake pad blank. Unit area pressure: 40Mpa, pressing temperature: 150℃, exhaust gas program: pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 150 seconds;

[0102] Step 3: Resin curing: The brake pad blank composite-formed in step 2 is fully cured in a program-controlled temperature furnace. The total curing time is 9 hours and the maximum curing temperature is 230 degrees Celsius.

[0103] Step 4: Post-processing: The solidified brake pad blank is processed on a 5-station combination grinder according to the design drawings through rough grinding, grooving, left chamfering, right chamfering and fine grinding. The processed brake pad undergoes infrared ablation, plastic powder electrostatic spraying, and riveting of silencers, alarms, springs, and coding and printing processes to finally obtain the brake pad.

[0104] Example 3

[0105] The raw materials provided are: 20 parts of modified phenolic resin (including 18 parts of molybdenum modified phenolic resin and 2 parts of melamine modified phenolic resin), 18 parts of metal reinforcing fiber (including 10 parts of steel fiber, 5 parts of aluminum fiber and 3 parts of zinc fiber), 19 parts of friction enhancer (including 3 parts of magnesium oxide, 10 parts of zirconium oxide, 2 parts of zirconium silicate, 2 parts of aluminum oxide and 2 parts of silicon carbide), 20 parts of filler (including 11 parts of precipitated barium sulfate, 2 parts of calcium carbonate, 2 parts of vermiculite, 2 parts of mica powder and 3 parts of diatomaceous earth) and 25 parts of graphite carbon powder A. Among them, the aspect ratio of steel fiber, zinc fiber and aluminum fiber in the metal reinforcing fiber is 150 and the length is 5 mm. The mass ratio of metal reinforcing fiber to modified phenolic resin is 0.9:1.

[0106] Step 1: Raw material mixing: weighing and mixing the raw materials prepared above in a plowshare mixer to obtain a brake pad mixture;

[0107] Step 2: Hot pressing composite molding: The mixed material obtained in step 1 and the glue-coated steel back are composited on an isotropic hot press to obtain a brake pad blank. Unit area pressure: 50Mpa, pressing temperature: 155℃, exhaust gas program: pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 10 seconds - pressure relief and exhaust for 5 seconds - pressurizing for 150 seconds;

[0108] Step 3: Resin curing: The brake pad blank composite-formed in step 2 is fully cured in a program-controlled temperature furnace. The total curing time is 9 hours and the maximum curing temperature is 230 degrees Celsius.

[0109] Step 4: Post-processing: The solidified brake pad blank is processed on a 5-station combination grinder according to the design drawings through rough grinding, grooving, left chamfering, right chamfering and fine grinding. The processed brake pad undergoes infrared ablation, plastic powder electrostatic spraying, and riveting of silencers, alarms, springs, and coding and printing processes to finally obtain the brake pad.

[0110] Example 4

[0111] It is basically the same as Example 3, except that the raw materials and the number of portions are as follows:

[0112] 20 parts of modified phenolic resin (including 18 parts of molybdenum modified phenolic resin and 2 parts of melamine modified phenolic resin), 10 parts of metal reinforcing fiber (including 5 parts of steel fiber, 3 parts of aluminum fiber and 2 parts of zinc fiber), 19 parts of friction enhancer (including 3 parts of magnesium oxide, 10 parts of zirconium oxide, 2 parts of zirconium silicate, 2 parts of aluminum oxide and 2 parts of silicon carbide), 20 parts of filler (including 11 parts of precipitated barium sulfate, 2 parts of calcium carbonate, 2 parts of vermiculite, 2 parts of mica powder and 3 parts of diatomaceous earth) and 25 parts of graphite carbon powder A. Among them, the aspect ratio of steel fiber, zinc fiber and aluminum fiber in the metal reinforcing fiber is 150 and the length is 5 mm. The mass ratio of metal reinforcing fiber to modified phenolic resin is 0.5:1.

[0113] Example 5

[0114] It is basically the same as Example 3, except that the raw materials and the number of portions are as follows:

[0115] 20 parts of modified phenolic resin (including 18 parts of molybdenum modified phenolic resin and 2 parts of melamine modified phenolic resin), 25 parts of metal reinforcing fiber (including 10 parts of steel fiber, 10 parts of aluminum fiber and 5 parts of zinc fiber), 19 parts of friction enhancer (including 3 parts of magnesium oxide, 10 parts of zirconium oxide, 2 parts of zirconium silicate, 2 parts of aluminum oxide and 2 parts of silicon carbide), 20 parts of filler (including 11 parts of precipitated barium sulfate, 2 parts of calcium carbonate, 2 parts of vermiculite, 2 parts of mica powder and 3 parts of diatomaceous earth) and 25 parts of graphite carbon powder A. Among them, the aspect ratio of steel fiber, zinc fiber and aluminum fiber in the metal reinforcing fiber is 150 and the length is 5 mm. The mass ratio of metal reinforcing fiber to modified phenolic resin is 1.25:1.

[0116] Example 6

[0117] It is basically the same as Example 3, except that in the metal reinforced fibers of Comparative Example 3, the aspect ratios of the steel fibers, copper fibers and aluminum fibers are all 200, and the lengths are 5 mm.

[0118] Example 7

[0119] It is basically the same as Example 3, except that in the metal reinforced fibers of Comparative Example 3, the aspect ratios of the steel fibers, copper fibers and aluminum fibers are all 150, and the lengths are 9 mm.

[0120] Comparative Example 1

[0121] It is basically the same as Example 3, except that the graphite powder A in Example 1 is replaced with an equal mass of graphite powder B. The graphite powder B is derived from Hubei Juneng Graphite Co., Ltd. 7210-B, with a fixed carbon content of 99.32%, a thermal conductivity of 150-200 W / m·degree, and a particle size of 63 μm-125 μm.

[0122] Comparative Example 2

[0123] It is basically the same as Example 3, except that in the metal reinforced fibers of Comparative Example 3, the aspect ratios of the steel fibers, copper fibers and aluminum fibers are all 100, and the lengths are 5 mm.

[0124] Comparative Example 3

[0125] It is basically the same as Example 3, except that the raw materials and the number of portions are as follows:

[0126] 20 parts of modified phenolic resin (including 18 parts of molybdenum modified phenolic resin and 2 parts of melamine modified phenolic resin), 40 parts of metal reinforcing fiber (including 20 parts of steel fiber, 10 parts of aluminum fiber and 10 parts of zinc fiber), 19 parts of friction enhancer (including 3 parts of magnesium oxide, 10 parts of zirconium oxide, 2 parts of zirconium silicate, 2 parts of aluminum oxide and 2 parts of silicon carbide), 20 parts of filler (including 11 parts of precipitated barium sulfate, 2 parts of calcium carbonate, 2 parts of vermiculite, 2 parts of mica powder and 3 parts of diatomaceous earth) and 25 parts of graphite carbon powder A. Among them, the aspect ratio of steel fiber, zinc fiber and aluminum fiber in the metal reinforcing fiber is 150 and the length is 5 mm. The mass ratio of metal reinforcing fiber to modified phenolic resin is 2:1.

[0127] The brake pads prepared in each embodiment and comparative example were subjected to physical property tests, specifically: a density test using the drainage method was performed according to GB / T1463-2005, an internal shear strength test was performed according to GB / T 26739-2011, and a thermal conductivity test was performed according to ASTM-D5470. The test results are shown in Table 1.

[0128] Table 1

[0129]

[0130] It can be seen from Table 1 that the thermal conductivity of the brake pad prepared in the embodiment is higher than that in the comparative example.

[0131] The brake pads prepared in the embodiments and comparative examples were combined with a carbon-ceramic brake disc with a diameter of 380 mm to form a carbon-ceramic friction pair, and the friction characteristics test was carried out on a Link300 inertia test bench, specifically: the friction coefficient of the brake pad at different braking temperatures was measured and investigated according to SAE standard J2522, with a starting temperature of 80°C; the friction coefficient at different braking speeds and the wear rate were measured (the thickness of the friction pad before and after the test was measured with a micrometer, and the thickness difference of the friction pad before and after the test was taken). The test results are shown in Table 2.

[0132] Table 2

[0133]

[0134] It can be seen from Table 2 that, compared with the comparative example, the carbon-ceramic friction pair consisting of the brake pad prepared in the embodiment and the carbon-ceramic brake disc with a diameter of 380 mm has a higher friction coefficient and a higher stability of the friction coefficient.

[0135] High temperature decay test: Use a K-type thermocouple to measure the maximum temperature 2mm below the friction surface of the brake pad through a drilled hole on the side of the brake pad: According to the SAE standard J2522 test procedure, the test procedure includes two high temperature decay tests. Ten braking cycles are performed in the decay test. During these 10 braking cycles, the friction temperature rise will cause the friction surface and shallow surface layer of the brake pad to have very high temperatures. If the thermal conductivity of the brake pad is high, it is easier to quickly transfer the heat from the friction surface and shallow surface layer to the deep part of the brake pad, thereby protecting the friction surface. By testing the temperature rise 2mm below the shallow surface of the friction surface of the brake pad, the thermal conductivity of the brake pad can be indirectly fed back. The temperature 2mm below the shallow surface of the friction surface in two high temperature decay tests is shown in Table 3.

[0136] Table 3

[0137]

[0138] It can be seen from Table 3 that, compared with the comparative example, the brake pad prepared in the embodiment has a lower maximum temperature at 2 mm below the shallow surface of the friction surface in the high temperature decay test, and has a stronger surface thermal conductivity.

[0139] From the above, it can be seen that the invention applies modified phenolic resin, metal reinforcing fiber, friction enhancer, filler and graphite powder with three-dimensional layered structure in specific proportions, and controls the aspect ratio and length of the metal reinforcing fiber, as well as the thermal conductivity of the graphite powder. The interaction of various characteristics can effectively improve the thermal conductivity and friction coefficient of the friction material, effectively improve the stability of the friction coefficient, and effectively suppress the rapid temperature rise of the friction surface, effectively solving the problem of the reduction of braking performance of the brake pad due to the excessive temperature rise of the traditional carbon-ceramic friction pair.

[0140] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0141] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A friction material, characterized in that: By mass, it includes the following components: 15-25 parts of phenolic resin, 10-20 parts of metal reinforcing fiber, 10-25 parts of friction enhancer, 10-40 parts of filler and 20-30 parts of graphite carbon powder; the aspect ratio of the metal reinforcing fiber is 150-200, the length is 5 mm-9 mm, the graphite carbon powder has a three-dimensional layered structure, and the thermal conductivity of the graphite carbon powder is 400-600 W / m·degree.

2. The friction material according to claim 1, characterized in that: By mass, it includes the following components: 18-22 parts of phenolic resin, 12-18 parts of metal reinforcing fiber, 11-24 parts of friction enhancer, 20-30 parts of filler and 24-30 parts of graphite carbon powder.

3. The friction material according to claim 1, characterized in that: The mass ratio of the metal reinforcing fiber to the modified phenolic resin is 0.5-1.25:

1.

4. The friction material according to claim 1, characterized in that: The metal reinforcing fiber includes at least one of steel fiber, copper fiber, aluminum fiber and zinc fiber.

5. The friction material according to claim 1, characterized in that: The particle size of the graphite carbon powder is 5 μm to 10 μm; and / or The graphitization degree of the graphite carbon powder is 90% to 96%.

6. The friction material according to any one of claims 1 to 5, characterized in that: The phenolic resin comprises a modified phenolic resin, and the modified phenolic resin comprises at least one of a molybdenum-modified phenolic resin, a boron-modified phenolic resin, an aniline-modified phenolic resin and a melamine-modified phenolic resin; and / or The particle size of the phenolic resin is 50 μm to 80 μm.

7. The friction material according to any one of claims 1 to 5, characterized in that: The friction enhancer comprises at least one of magnesium oxide, zirconium oxide, red iron oxide, black iron oxide, zirconium silicate, brown corundum, aluminum oxide and silicon carbide; and / or The filler includes at least one of talc powder, precipitated barium sulfate, barite powder, calcium carbonate, calcium hydroxide, mica powder, vermiculite powder, kaolin, diatomaceous earth, antimony sulfide and tin sulfide.

8. A method for preparing a friction material, characterized in that: The following steps are involved: Providing raw materials according to the components of the friction material according to any one of claims 1 to 7; The various raw materials are mixed to obtain a friction material.

9. A brake pad, characterized in that: The friction material comprises the friction material as described in any one of claims 1 to 8.

10. A brake friction pair, characterized in that: Comprising the brake pad as claimed in claim 9.

11. A means of transport, characterized in that: The invention comprises at least one of the brake pad as claimed in claim 9 and the brake friction pair as claimed in claim 10.